1998
DOI: 10.1038/sj.onc.1202197
|View full text |Cite
|
Sign up to set email alerts
|

The BCL-6 POZ domain and other POZ domains interact with the co-repressors N-CoR and SMRT

Abstract: Virtually all diuse large cell lymphomas and a signi®cant fraction of follicular lymphomas contain translocations and/or point mutations in the 5' noncoding region of the putative oncogene BCL-6, that are presumed to deregulate its expression. BCL-6 encodes a Cys 2 -His 2 zinc ®nger transcriptional repressor with a POZ domain at its amino-terminus. The POZ (or BTB) domain, a 120-amino-acid motif, mediates homomeric and, in some proteins, heteromeric POZ-POZ interactions. In addition, the POZ domain is required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
273
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 296 publications
(279 citation statements)
references
References 43 publications
5
273
1
Order By: Relevance
“…Interestingly, the Znfg derivative is nuclear (Figure 1c), indicating that the zinc ®nger region contains at least one of the nuclear targeting signals of BCL6. In contrast to full length BCL6fg, Znfg does not produce regular spherical nuclear substructures ( Figure 1c; Dhordain et al, 1995;Huynh and Bardwell, 1998), but a di use nuclear staining sometimes superimposed by irregularly shaped nuclear areas of stronger concentration ( Figure 1c). As expected, Znfg binds very e ciently to the B6BS probe (Chang et al, 1996; data not shown) but fails to repress via this sequence ( Figure 2).…”
Section: Generation Of Bcl6fg and Bcl6d1-514fg Inducible Cell Linesmentioning
confidence: 93%
See 4 more Smart Citations
“…Interestingly, the Znfg derivative is nuclear (Figure 1c), indicating that the zinc ®nger region contains at least one of the nuclear targeting signals of BCL6. In contrast to full length BCL6fg, Znfg does not produce regular spherical nuclear substructures ( Figure 1c; Dhordain et al, 1995;Huynh and Bardwell, 1998), but a di use nuclear staining sometimes superimposed by irregularly shaped nuclear areas of stronger concentration ( Figure 1c). As expected, Znfg binds very e ciently to the B6BS probe (Chang et al, 1996; data not shown) but fails to repress via this sequence ( Figure 2).…”
Section: Generation Of Bcl6fg and Bcl6d1-514fg Inducible Cell Linesmentioning
confidence: 93%
“…The induced UTA-L2 and UTA-Z2 cells gave a pattern indistinguishable from that obtained in induced UTA-L1 cells and induced UTA-Z1 cells, respectively (not shown). Right: the same cultures were stained with DAPI to visualize the nuclei Huynh and Bardwell, 1998). Note that in UTA-L1 or UTA-L2 undergoing mitosis, the BCL6fg staining gives a di use cytoplasmic and nuclear signal superimposed by dots in both compartments (Figure 1c).…”
Section: Generation Of Bcl6fg and Bcl6d1-514fg Inducible Cell Linesmentioning
confidence: 99%
See 3 more Smart Citations